2015
DOI: 10.1007/s00268-015-3349-1
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Asymptomatic Papillary Thyroid Microcarcinoma: Time‐Dependent Changes in Calcification and Vascularity During Active Surveillance

Abstract: PMCs in older patients showed significantly stronger calcification patterns and poorer vascularity. Both consolidation of calcification and loss of vascularity occurred in a time-dependent manner during observation and were significant indicators for non-progressive disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
119
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(126 citation statements)
references
References 35 publications
(40 reference statements)
2
119
1
1
Order By: Relevance
“…Concerning macrocalcification, one group has already reported a similar observation that strong calcification detected by ultrasonography during active surveillance was related to non-progressive disease [28]. However, it is not easy to correctly diagnose follicular variants of PTC from aspirated materials.…”
Section: Discussionmentioning
confidence: 82%
“…Concerning macrocalcification, one group has already reported a similar observation that strong calcification detected by ultrasonography during active surveillance was related to non-progressive disease [28]. However, it is not easy to correctly diagnose follicular variants of PTC from aspirated materials.…”
Section: Discussionmentioning
confidence: 82%
“…It was recently reported that PMCs with a rich blood supply or a lack of strong calcification on ultrasound have stronger growth activity [8]. However, in that study's series, no patients showed life-threatening tumor progression during the active surveillance or after the rescue surgery.…”
Section: (4) Is Thyroid-stimulating Hormone (Tsh) Suppression Useful mentioning
confidence: 80%
“…He also suspected that a rescue surgery performed after the detection of signs of PMC progression (such as size enlargement and the novel appearance of node metastases) is not too late and would not influence patients' prognoses. In 1995, Cancer Institute Hospital (Tokyo, Japan) also initiated an active surveillance program for low-risk PMCs, and these two institutions have published promising data using large patient series [3][4][5][6][7][8][9]. thereafter to determine whether novel lymph node metastases or size enlargement are present.…”
Section: History Of the Active Surveillance Of Pmcsmentioning
confidence: 99%
“…Abundant tumor vasculature, for example, is a feature associated with higher growth, while scarce vascularization and calcifications are associated with non-progressive tumors. 12 Molecular markers (BRAF, PIK3CA, AKT1, TERT, TP53) may be useful in the future for prognostic stratification, especially the coexistence of these markers [13][14][15][16] as well as the expression of the Ki67 protein, which is associated with PTMC size, tumor invasion, lymph node metastasis, and may be used in the future as a monitoring and a clinical decision parameter. 17 In the group of patients with low-risk PTMC that demand surgery during the follow-up (<10% of cases), it does not impact on the outcome.…”
mentioning
confidence: 99%